2004
DOI: 10.2337/diabetes.53.suppl_3.s190
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Inhibitory Polypeptide and Glucagon-Like Peptide-1 in the Pathogenesis of Type 2 Diabetes

Abstract: The incretin effect denominates the phenomenon that oral glucose elicits a higher insulin response than does intravenous glucose. The two hormones responsible for the incretin effect, glucose-dependent insulinotropic hormone (GIP) and glucagon-like peptide-1 (GLP-1), are secreted after oral glucose loads and augment insulin secretion in response to hyperglycemia. In patients with type 2 diabetes, the incretin effect is reduced, and there is a moderate degree of GLP-1 hyposecretion. However, the insulinotropic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
133
2
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(144 citation statements)
references
References 80 publications
5
133
2
3
Order By: Relevance
“…The blunted insulin response to the meal may be a consequence of a reduction in the plasma concentration of GIP and GLP-1. It has been reported that the effect of incretins can account for roughly 20 -60% of the total insulin secretory response to a meal (28). Interestingly, despite significantly greater incretin response (especially a robust increase in GIP) during the first hour after our control compared with low-fat meals, plasma insulin concentration was not different.…”
Section: Discussioncontrasting
confidence: 48%
“…The blunted insulin response to the meal may be a consequence of a reduction in the plasma concentration of GIP and GLP-1. It has been reported that the effect of incretins can account for roughly 20 -60% of the total insulin secretory response to a meal (28). Interestingly, despite significantly greater incretin response (especially a robust increase in GIP) during the first hour after our control compared with low-fat meals, plasma insulin concentration was not different.…”
Section: Discussioncontrasting
confidence: 48%
“…In our study, because both b-hydroxybutyrate and glucose concentration might be elevated in the MCT-fed group, the plasma insulin concentration was higher in the MCT-fed group than in the LCT-fed group. Insulin secretion is known to be regulated by glucose-dependent insulinotropic polypeptide (GIP), one of gut-derived insulinotropic agents (32). In this context, MCT has not been found effective in stimulating GIP release (33).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand defective or blunted GLP-1 secretion has been reported in type 2 diabetes on some occasions [23,[33][34][35]. Despite these observations of impaired GLP-1 secretion in type 2 diabetes GLP-1-based therapies retain an ability to stimulate insulin secretion from pancreatic beta-cells [15].…”
Section: Introductionmentioning
confidence: 86%
“…The functioning of the enteroinsular axis is markedly affected by the onset of type 2 diabetes. On one hand there is clear evidence of impaired GIP action but not GIP secretion [15,23,[34][35].…”
Section: Introductionmentioning
confidence: 99%